Revamping Higher Education in Vietnam: Obstacles and Remedies - CAO, Ngoc Bau; TRAN, Mong Nghi (Journal of Ecohumanism, 2024)
This study analyzes the present condition of higher education reform in Vietnam and suggests remedies to tackle significant obstacles. By utilizing contemporary policy documents and research, we examine the advancements made in implementing extensive changes, as well as the ongoing challenges in areas such as curriculum, teaching methodologies, research productivity, and university independence. Our research suggests that while there have been some good advancements, the quality of Vietnamese higher education still falls short of regional benchmarks in various significant areas. We contend that Vietnamese universities require more profound alterations in educational philosophy, institutional governance, faculty development, and international integration in order to enhance their quality and competitiveness. The paper ends with policy recommendations aimed at expediting the reform process.